Combination of Amphotericin B and Flucytosine against Neurotropic Species of Melanized Fungi Causing Primary Cerebral Phaeohyphomycosis - Deng, S. (2016)
Primary central nervous system phaeohyphomycosis is a fatal fungal infection due mainly to the neurotropic melanized fungiCladophialophora bantiana,Rhinocladiella mackenziei, andExophiala dermatitidis.Despite the combination of surgery with antifungal treatment, the prognosis continues to be poor, with mortality rates ranging from 50 to 70%. Therefore, a search for a more-appropriate therapeutic approach is urgently needed. Ourin vitrostudies showed that with the combination of amphotericin B and flucytosine against these species, the median fractional inhibitory concentration (FIC) indices for strains ranged from 0.25 to 0.38, indicating synergy. By use of Bliss independence analysis, a significant degree of synergy was confirmed for all strains, with the sum ΔE ranging from 90.2 to 698.61%. No antagonism was observed. These results indicate that amphotericin B, in combination with flucytosine, may have a role in the treatment of primary cerebral infections caused by melanized fungi belonging to the orderChaetothyriales Furtherin vivostudies and clinical investigations to elucidate and confirm these observations are warranted.